A review of the management of inflow water, wastewater and water reuse by membrane technology for a sustainable production in shrimp farming. (June 2018) - Ng, Law Yong; Ng, Ching Yin; Mahmoudi, Ebrahim; Ong, Chin Boon; Mohammad, Abdul Wahab
Graphical abstract: Highlights: The minimization of wastewater discharge from shrimp farming activities. Membrane technology can be suggested to improve aquaculture water quality. Recirculation of aquaculture water with improved water quality conditions. Abstract: The growth of the human population, shrinking seafood supply and polluted seawater are amongst the reasons that have encouraged a more stringent practice of water management in the aquaculture industry. The productivity of cultured shrimps is greatly restricted by limited access to "clean" seawater for aquaculture areas, however, which lack leads to severe disease outbreaks and reduced shrimp survival rates. Water management has thus become the core issue for increasing shrimp production by reducing the contamination from fresh water intake, fresh water usage and aquaculture wastewater discharge. The objective of this study is to evaluate the feasibility of setting up an integrated recirculating aquaculture system using the membrane technology, which possibly utilizes microfiltration, ultrafiltration, nanofiltration or reverse osmosis modules, to improve the quality of aquaculture water while minimize the wastewater discharge and increase the water reuse. Feasibility of the integrated recirculating aquaculture system will be evaluated based on the effectiveness of improvement on the aquaculture water quality and limitations of the current membrane technologies. This study is highly useful for the researchers to modify the membrane characteristics before they are adopted in aquaculture water management system.